Oath taking ceremony dean's award / Syahida Fathiah Ahmad Kamal - Ahmad Kamal, Syahida Fathiah (Faculty of Pharmacy, 2024)
The Oath Taking Ceremony and Dean's Award, held on July 3, 2024, is a significant occasion in the faculty, marking a pivotal moment in the lives of students and honouring their outstanding achievements. This event not only recognises the hard work and dedication of the students but also instils a sense of responsibility and ethical commitment as they embark on their professional journeys.